Positive attitudes toward adoption of a multi-component intervention strategy aimed at improving HIV outcomes among adolescents and young people in Nampula, Mozambique: perspectives of HIV care providers - Phepo Mogoba; Maia Lesosky; Elton E. Mukonda; Allison Zerbe; Joana Falcao; Ricardino Zandamela; Landon Myer; Elaine J. Abrams (BMC, 2023)
Abstract Background Service providers' attitudes toward interventions are essential for adopting and implementing novel interventions into healthcare settings, but evidence of evaluations in the HIV context is still limited. This study is part of the CombinADO cluster randomized trial (ClinicalTrials.gov NCT04930367), which is investigating the effectiveness of a multi-component intervention package (CombinADO strategy) aimed at improving HIV outcomes among adolescents and young adults living with HIV (AYAHIV) in Mozambique. In this paper we present findings on key stakeholder attitudes toward adopting study interventions into local health services. Methods Between September and December 2021, we conducted a cross-sectional survey with a purposive sample of 59 key stakeholders providing and overseeing HIV care among AYAHIV in 12 health facilities participating in the CombinADO trial, who completed a 9-item scale on attitudes towards adopting the trial intervention packages in health facilities. Data were collected in the pre-implementation phase of the study and included individual stakeholder and facility-level characteristics. We used generalized linear regression to examine the associations of stakeholder attitude scores with stakeholder and facility-level characteristics. Results Overall, service-providing stakeholders within this setting reported positive attitudes regarding adopting intervention packages across study clinic sites; the overall mean total attitude score was 35.0 ([SD] = 2.59, Range = [30-41]). The study package assessed (control or intervention condition) and the number of healthcare workers delivering ART care in participating clinics were the only significant explanatory variables to predict higher attitude scores among stakeholders (β = 1.57, 95% CI = 0.34-2.80, p = 0.01 and β = 1.57, 95% CI = 0.06-3.08, p = 0.04 respectively). Conclusions This study found positive attitudes toward adopting the multi-component CombinADO study interventions among HIV care providers for AYAHIV in Nampula, Mozambique. Our findings suggest that adequate training and human resource availability may be important in promoting the adoption of novel multi-component interventions in healthcare services by influencing healthcare provider attitudes.